1994
DOI: 10.1021/ma00089a017
|View full text |Cite
|
Sign up to set email alerts
|

Organic NLO Polymers. 2. A Study of Main-Chain and Guest-Host NLO Polymers: NLO-phore Structure Versus Poling

Abstract: Several new dipolar main-chain (2) nonlinear optical (NLO) polymers were prepared. The NLO-phores, based on alkoxy substituted -cyanoacrylates, were also placed as monomeric guests within a poly(methyl methacrylate) host. Polar alignment of the NLO-phores by corona poling and their relaxation behavior was monitored by detecting the optical signal resulting from the second harmonic generation. The study revealed that two dipolar rigid-rod main-chain NLO polymers (NLOPs), having solubilizing side chains, were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 4 publications
(11 reference statements)
0
14
0
Order By: Relevance
“…Köhler et al 12,13) studied the relaxation of electric field induced polar orientation in main-chain polymers. Stenger-Smith et al 65,66) , Lindsay et al 67) , Wrigth et al 68,69) and Liu et al 70) also synthesized main-chain polymers, but the reported second-order susceptibilites were low (0.17 pm/V). A polyurethane main-chain polymer with dialkylamino sulfonyl azobenzene incorporated in the main chain was studied by Xu et al 71) They measured a d 33 (-2 x; x, x) value of 40 pm/V (T g not given, poled at 115 8C, excitation at 1 064 nm).…”
Section: Main-chain Polymersmentioning
confidence: 99%
“…Köhler et al 12,13) studied the relaxation of electric field induced polar orientation in main-chain polymers. Stenger-Smith et al 65,66) , Lindsay et al 67) , Wrigth et al 68,69) and Liu et al 70) also synthesized main-chain polymers, but the reported second-order susceptibilites were low (0.17 pm/V). A polyurethane main-chain polymer with dialkylamino sulfonyl azobenzene incorporated in the main chain was studied by Xu et al 71) They measured a d 33 (-2 x; x, x) value of 40 pm/V (T g not given, poled at 115 8C, excitation at 1 064 nm).…”
Section: Main-chain Polymersmentioning
confidence: 99%
“…Therefore, the idea arose [6][7][8] not to simply disperse these molecules in the matrix but to graft them on the inner surface of its pores through covalent bonds. In a similar way, recent works on doped organic polymers have proven the great interest of such a grafting [9] for nonlinear optical properties. In our case, this ought to allow much higher concentrations in dye molecules in the gel without segregation, and thus should lead to higher birefringences.…”
Section: Introductionmentioning
confidence: 78%
“…Here the spacer is the chain --(CHz)3--NH--CS--NH--, which length seems large enough to ensure the movements of the grafted rhodamine B molecule. It is important here to point out the importance of the flexibility of the spacer for the alignment of the dopants, as previous studies led on doped organic polymers have established it [9].…”
Section: Sample Preparationmentioning
confidence: 98%
See 1 more Smart Citation
“…There are tremendous challenges in the design and synthesis of polymers with large NLO effects. Polyesters,8–10 polyurethanes,11–15 polyamides,16, 17 and poly(phenylene ethynylene)s18 containing a chromophoric main chain have been prepared. Various polymers with NLO‐chromophores in the side chain, such as poly(meth)acrylates,19–23 polystyrene24 and polyimides25–28 have also been reported.…”
Section: Introductionmentioning
confidence: 99%